2013
DOI: 10.3354/dao02592
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in amphibian populations inhabiting agroecosystems in northeastern Buenos Aires Province, Argentina

Abstract: The occurrence of abnormalities in amphibians has been reported in many populations, and its increase could be related to environmental pollution and habitat degradation. We evaluated the type and prevalence of abnormalities in 5 amphibian populations from agroecosystems with different degrees of agricultural disturbance (cultivated and reference areas). We detected 9 types of abnormalities, of which the most frequent were those occurring in limbs. The observed prevalence of abnormality in assessed populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
3
33
0
4
Order By: Relevance
“…After flooding, tadpoles complete their development in proximate water bodies (Lavilla et al 2000). Agostini et al (2013) also suggested a link between the prevalence and types of malformation and the levels of exposure to malformation factors during early stages and the habits of juveniles and adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After flooding, tadpoles complete their development in proximate water bodies (Lavilla et al 2000). Agostini et al (2013) also suggested a link between the prevalence and types of malformation and the levels of exposure to malformation factors during early stages and the habits of juveniles and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Attademo et al 2005, Guerra & Aráoz 2015. The variation of prevalence and types of malformation between them could result from differences in their natural history (Johnson et al 2001a, Agostini et al 2013) and consequently in their sensitivity (e.g. Relyea 2009, Attademo et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soybeans crops replaced lands for livestock, expanding the agricultural frontier to areas previously not been reported in areas of accelerated replacement; these changes are mainly associated with pesticide pollution of wetlands and aquifers, and habitat loss (Herrera et al 2013). Studies conducted in croplands of this region have documented that members of amphibian populations have debilitated bodies, enzymatic alterations (Brodeur et al 2011), and high prevalences of abnormalities (Agostini et al 2013). Additionally, application of common pesticides cause lethal and sublethal effects on tadpoles (Agostini et al 2009, Agostini 2013.…”
Section: Introductionmentioning
confidence: 99%